Efficient Approaches to the Design of Six-Membered Polyazacyclic Compounds—Part 1: Aromatic Frameworks - Elena A. Gyrgenova; Yuliya Y. Titova; Andrey V. Ivanov (Molecules)
This review summarises the possible applications and basic methodologies for the synthesis of six-membered polyazo heterocycles, namely, diazines, triazines, and tetrazines. The time period covered by the analysed works ranges from the beginning of the 20th century to the present day. This period was chosen because it was during this time that synthetic chemistry, as defined by physicochemical research methods, became capable of solving such complex problems as efficiently as possible. The first part of the review describes the applications of polyazo heterocyclic compounds, whose frameworks are found in the composition of drugs, dyes, and functional molecules for materials chemistry, as well as in a wide variety of natural compounds and their synthetic analogues. The review also systematises the methods for assembling six-membered aromatic polyazo heterocycles, including intramolecular and sequential cyclisation, which determine the possible structural and functional diversity based on the presence and arrangement of nitrogen atoms and the position of the corresponding substituents.